Lp solutions of anticipated backward stochastic differential equations under monotonicity and general increasing conditions. Issue 2 (17th February 2016) - Hu, Feng; Chen, Zengjing
Abstract : In this paper, we deal with a class of anticipated backward stochastic differential equations (anticipated BSDEs) under weak assumptions on the coefficients. We prove the existence and uniqueness result for solutions of anticipated BSDEs under monotonicity and general increasing conditions on, with Lipschitz on . Furthermore, we give several comparison theorems with respect to 1-dimensional anticipated BSDEs.